Análisis Científico de la Ética desde la Perspectiva Multidisciplinaria - Herrera-Sánchez, Maybelline Jaqueline (Editorial Grupo AEA, 2022)
This manuscript is the result of multidisciplinary research under different scientific-academic perspectives, through the confrontation of criteria of different authors under a descriptive approach that points out the importance of ethics in various current scenarios such as discrimination against women in the workplace, the management of individuals within organizations, The study also shows how ethics affects the organizational climate and teaching management in the case study of a university, ethics and corporate social responsibility as a challenge for companies, labor discrimination as unethical behavior in the area of human resources, and finally, a comparison of ethics in corporate advertising. These studies are carried out from a scientific point of view and are approached to the Ecuadorian reality.